2023
DOI: 10.1097/md.0000000000033189
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of Baihe Dihuang decoction in treating menopausal syndrome based on network pharmacology

Abstract: Menopausal syndrome (MS) refers to a series of symptoms with autonomic nervous system dysfunction caused by decreased sex hormones before and after menopause. Baihe Dihuang (BHDH) decoction positively affects MS, but its mechanism remains unclear. This study aimed to reveal the underlying mechanism through network pharmacology. The components of the BHDH Decoction were found through HERB, while corresponding targets were obtained from the HERB, Drug Bank, NPASS, Targetnet, and Swisstarget databases. The MS tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…KEGG pathway [32] analysis was applied to the selected genes to visualize the ErbB signaling pathway as shown in Figure 5. Tian et al reported the ErbB signaling pathway in association with the menopausal syndrome in their ontological analysis [33]. Pei et al found a cardiorenal disease connection during postmenopause with ErbB signaling pathway genes [34], which sparked the idea of the survival analysis of the two cohorts in our work.…”
Section: Discussionmentioning
confidence: 57%
“…KEGG pathway [32] analysis was applied to the selected genes to visualize the ErbB signaling pathway as shown in Figure 5. Tian et al reported the ErbB signaling pathway in association with the menopausal syndrome in their ontological analysis [33]. Pei et al found a cardiorenal disease connection during postmenopause with ErbB signaling pathway genes [34], which sparked the idea of the survival analysis of the two cohorts in our work.…”
Section: Discussionmentioning
confidence: 57%
“…The Omicshare database (https://www.omicshare.com, accessed on 29 March 2023) was used to perform the GO (gene ontology) function and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis on differential proteins [43].…”
Section: Potential Target Pathway Analysismentioning
confidence: 99%